Species with forest agroforestry potential areas for highlands in the department of Nariño - Muñoz, Diego Andrés; Calvache, David Andrés; Yela, José Fernando (Revista de Ciencias Agrícolas, 2013)
This work was conducted in 12 municipalities in the department of Nariño, Colombia, located between 2600 and 3200 m, characterized by presenting traditional agroforestry systems, in order to identify and describe forest species that could have potential for agroforestry in the department of Narino. Primary data were collected through surveys, interviews, photographic records and recollection of botanicals specimens, which were complemented with secondary information, using the methodology of theoretical sampling (Glaser & Strauss, 1967). As result of the above procedure, 40 forestal species were registered of native and exotic that showed a good potential for agroforestry, classified as 21 useful for living fences, eight (8) as scattered trees and 11 for home gardens; it was determined that knowledge is varied and poorly developed, having a better knowledge for those species that represent an economic benefit to the producer.